(untitled) (Western European Journal of Medicine and Medical Science, 2024)
In recent years, the role of nutrition in the prevention and occurrence of a large group of chronic non-communicable diseases in the population of developed countries has been determined more precisely. It has been proven that the increase in the number of diseases associated with overweight and obesity, atherosclerosis, hypertension, decreased glucose tolerance, metabolic disorders, and secondary immunodeficiencies is due to several “external” factors, the leading of which are rapid non-evolutionary changes in nutrition (changes in the ratio of the main nutrient groups) and lifestyle changes (decreasing physical activity and increasing stress). The fundamental reasons for changes in nutrition are recognized as industrialization, urbanization and globalization of the food and services market, which have changed not only food production, but also the stereotype of food choice